PLAY BASED PRINCIPLE IN TEACHING ENGLISH TO VERY YOUNG LEARNERS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In today’s globalized world, foreign language proficiency is a valuable skill, and research shows that early language exposure has significant cognitive, social, and linguistic benefits. This research focuses on developing and implementing a play-based approach to teaching foreign languages to very young learners (age 6), leveraging their natural curiosity and love for play to foster language acquisition.The research was conducted experimentally with 60 students of a public kindergarten in Namangan, Uzbekistan, and teachers working in different kindergartens were asked to answer the survey question. The findings of the study showed that Play-based learning creates an engaging, enjoyable, and developmentally appropriate environment for children to acquire a new language.